Multiomic analysis and immunoprofiling reveal distinct subtypes of human angiosarcoma - Chan, Jason Yongsheng; Lim, Jing Quan; Yeong, Joe; Ravi, Vinod; Guan, Peiyong; Boot, Arnoud; Tay, Timothy Kwang Yong; Selvarajan, Sathiyamoorthy; Md Nasir, Nur Diyana; Loh, Jie Hua; Ong, Choon Kiat; Huang, Dachuan; et al. (Journal of Clinical Investigation, 2020)
Angiosarcomas are rare, clinically aggressive tumors with limited treatment options and a dismal prognosis. We analyzed angiosarcomas from 68 patients, integrating information from multiomic sequencing, NanoString immuno-oncology profiling, and multiplex immunohistochemistry and immunofluorescence for tumor-infiltrating immune cells. Through whole-genome sequencing (n = 18), 50% of the cutaneous head and neck angiosarcomas exhibited higher tumor mutation burden (TMB) and UV mutational signatures; others were mutationally quiet and non-UV driven. NanoString profiling revealed 3 distinct patient clusters represented by lack (clusters 1 and 2) or enrichment (cluster 3) of immune-related signaling and immune cells. Neutrophils (CD15+), macrophages (CD68+), cytotoxic T cells (CD8+), Tregs (FOXP3+), and PD-L1+ cells were enriched in cluster 3 relative to clusters 2 and 1. Likewise, tumor inflammation signature (TIS) scores were highest in cluster 3 (7.54 vs. 6.71 vs. 5.75, respectively; P < 0.0001). Head and neck angiosarcomas were predominant in clusters 1 and 3, providing the rationale for checkpoint immunotherapy, especially in the latter subgroup with both high TMB and TIS scores. Cluster 2 was enriched for secondary angiosarcomas and exhibited higher expression of DNMT1, BRD3/4, MYC, HRAS, and PDGFRB, in keeping with the upregulation of epigenetic and oncogenic signaling pathways amenable to targeted therapies. Molecular and immunological dissection of angiosarcomas may provide insights into opportunities for precision medicine.